Vpliv marketinških sposobnosti na porast inovativnosti v organizacijah - Završnik, Bruno (Organizacija (Kranj), 2006)
The paper presents the results of the role of marketing capabilities for the company's innovation. The research has encompassed the analysis of sources of marketing capabilities (in the areas of marketing communications), market research, appropriate sales force and new product development, can lead to higher innovation. As sources of competitive advantage, companies try to create their product or service differentiation by developing higher product or service quality, by using their knowledge to solving marketing problems, by communicating with their customers, and by satisfying customer's needs which also lead to better company's innovation.
Keywords: marketing; podjetja; trženje; tržno komuniciranje; inovacije; inovativno poslovanje; izboljšave